P89 You don't get a second chance to make a first impression…. (1st October 2013) - Finnerty, Jane; Haywood, Chris; Ellis, John; Turnbull, Ian; Jones, Debbie; Bennett, Pat
Abstract : Background/context: Fostering good first impressions of a care setting are an important component of building confidence and providing reassurance for patient's, carers, relatives and visitors. The 15 Steps Challenge is a toolkit devised by the NHS Institute for Innovation and Improvement in 2012 to help staff, patients and others to identify improvements that enhance the patient experience and environment. Initially 15 Steps was developed for use in Hospital wards but we adapted it for the whole Hospice environment. Aims: To use an accredited quality improvement tool and clear framework to facilitate in depth observations of quality care across four domains: Welcoming Safe Caring and Involvement Well organised and calm Approach used: Readily available easy to use literature to guide implementation PowerPoint slides for awareness sessions and training Small team to undertake the review (included 1 patient/carer representative, 1 non-clinical staff and 2 clinical staff) Dedicated toolkit Engagement with internal stakeholders A structured walk around the entirety of the Hospice environment Presentations to different staff groups on findings Focus on positive feedback and sharing good practice Repeated at 6 months to show achievements and improvements Outcomes: Explicit patient/carer perspectives were taken into account. Detailed action plans with key positive impacts on the working environment. Supports the Care Quality Commission's Essential Standards Case study for evaluation (IES) by telephone survey. Application to Hospice Practice: Use of the 15 Steps toolkit clearly effective as a quality improvement initiative Re-audit has shown improvements in all domains Heightened staff awareness; quality is everyone's business Strengthened communication across services Adaptable for use in Fundraising/Trading Company improving quality across the organisation. The Challenge can be repeated on a regular basis to cover all areas and to ensure that improvements are being progressed and maintained.